Can Blockchain Technology Address De-Risking in Emerging Markets? - Ramachandran, Vijaya (International Finance Corporation, Washington, DC, 2018)
Block chain, or distributed ledger technology, has the potential to address many problems in emerging markets. In this note the authors consider whether block chain can be used to mitigate the problem of de-risking by financial institutions, which affects receivers of remittances, businesses that need correspondent banking relationships, and charities working in conflict countries. Block chain is an evolving technology, and understanding its scope and limitations will be critical to employing it to address these and related issues.